Urgensi Sertifikasi Pulau-Pulau Kecil Terluar Dalam Rangka Menjaga Keutuhan Wilayah NKRI Sebagaimana Amanah Konstitusi (RechtJiva, 2024)
In this study, the author highlights issues related to the ineffectiveness of the Ministry of ATR/BPN in implementing Outermost Small Islands certification. Several regulations are a driving factor for the Government to immediately carry out certification for all Outermost Small Islands. However, in its implementation there are several obstacles in the certification process carried out by the Government. This issue is the author's focus in analyzing the implementation of Article 49 of Law Number 1 of 2004 Jo. Article 9 Paragraph (1) Ministerial Regulation Number 17 of 2016 relating to certification of Outermost Small Islands and obstacles to the Ministry of ATR/BPN in carrying out comprehensive certification. This is because there are 24 islands that have not been certified, which can provide a gap for other countries to be able to acquire and take over these Outermost Small Islands. The ATR/BPN Ministry, within its authority, has several obstacles, namely the location of the island which is difficult to reach, inefficient coordination between ministries, and a large budget for managing the natural resources found on the Outer Small Islands. The preparation of this thesis used empirical juridical research.